2022
DOI: 10.1021/acs.bioconjchem.2c00311
|View full text |Cite
|
Sign up to set email alerts
|

Advancing the Utility of DNA Origami Technique through Enhanced Stability of DNA-Origami-Based Assemblies

Abstract: Since its discovery in 2006, the DNA origami technique has revolutionized bottom-up nanofabrication. This technique is simple yet versatile and enables the fabrication of nanostructures of almost arbitrary shapes. Furthermore, due to their intrinsic addressability, DNA origami structures can serve as templates for the arrangement of various nanoscale components (small molecules, proteins, nanoparticles, etc.) with controlled stoichiometry and nanometerscale precision, which is often beyond the reach of other n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 158 publications
0
14
0
Order By: Relevance
“…In biological environments, the integrity of DNA NS can be rapidly compromised through attacks by various DNA nucleases (DNases), low divalent cation concentrations (common to nearly all physio-logical environments), and large variations in ionic strength and pH, particularly upon uptake into cells or ingestion into the stomach with its inherently acidic environment which is naturally hydrolytic. 39,40 For eventual therapeutic applications, a DNA NS must be sufficiently robust to maintain structural integrity long enough to enter the body, travel to a target of interest, and undergo any desired interactions, such as uptake, 57,58 The timescales for such interactions range from minutes to tens of hours, though most applications require lifetimes on the order of several hours in the body.…”
Section: Stability Of Dna Ns In Biological Environmentsmentioning
confidence: 99%
See 2 more Smart Citations
“…In biological environments, the integrity of DNA NS can be rapidly compromised through attacks by various DNA nucleases (DNases), low divalent cation concentrations (common to nearly all physio-logical environments), and large variations in ionic strength and pH, particularly upon uptake into cells or ingestion into the stomach with its inherently acidic environment which is naturally hydrolytic. 39,40 For eventual therapeutic applications, a DNA NS must be sufficiently robust to maintain structural integrity long enough to enter the body, travel to a target of interest, and undergo any desired interactions, such as uptake, 57,58 The timescales for such interactions range from minutes to tens of hours, though most applications require lifetimes on the order of several hours in the body.…”
Section: Stability Of Dna Ns In Biological Environmentsmentioning
confidence: 99%
“…In vitro studies have played a particularly outsized role in deciphering the relationship between DNA NS design and resilience in physiological environments, owing to the finegrained control of environmental conditions that cannot be achieved in vivo, as well as compatibility with large, multiplexed assays that can probe many design criteria and conditions simultaneously. Studies of the resilience of DNA NS against nucleases have shown that stability varies widely depending on the physical properties of the NS, as highlighted in several recent reviews, 32,39,40,[59][60][61] and structures with greater topological complexity, helical density, and crossover density have been shown to possess greater resistance to degradation by nucleases. [62][63][64] Unfortunately, DNA NS with these characteristics tend to possess reduced thermal stability and require higher divalent cation concentrations to remain stable in solution.…”
Section: Stability Of Dna Ns In Biological Environmentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the past decade has witnessed the successful application of DNA origami techniques in the biomedical field, several critical issues need to be addressed to fully realize its robust potential, in particular, for in vivo applications. One of the biggest challenges concerns the stability of DNA origami nanostructures under physiological conditions 99,100 . Ionic strength and nucleases in biological fluids have a great influence on the stability of DNA origami.…”
Section: Challenges For In Vivo Applications Of Dna Origamimentioning
confidence: 99%
“…One of the biggest challenges concerns the stability of DNA origami nanostructures under physiological conditions. 99,100 Ionic strength and nucleases in biological fluids have a great influence on the stability of DNA origami. Typically, DNA origami nanostructures are fabricated in the buffer system containing Mg 2+ at a concentration of 5-20 mM, 101,102 which is much higher than that in the blood (~1 mM) and tissue culture medium (<1 mM).…”
Section: Challenges For In Vivo Applications Of Dna Origamimentioning
confidence: 99%